Effect of 2-naphthyl-3- (3,4-dimethoxy) phenyl-propenoic acid on the metabolism of arachidonic acid in rabbit platelets - SUN Xiao-ming; XU Fu-ben; WU Yu-seng; LIN Chen-ren; GUO Chang-yan (Acta Pharmacologica Sinica; Vol 11, No 1 (January 1990): Acta Pharmacologica Sinica, 2016)
Washed rabbit platelets were incubated with [14C] arachidonic acid (AA sodium salt) after being exposed to 2-naphthyl-3-(3,4-dimethoxy) phenyl-propenoic acid (NM-PA), indomethacin (Ind) and imidazole (Imi) or control solvent. The metabolites of AA in rabbit platelets were separated with the system of chloroform: methanol: acetic acid: water (90:8:1:0.8) by thin layer chromatography and quantitated by liquid scintillation counter. The metabolism of AA was influenced by NMPA dose-dependently in the range of 0.05-0.5 mmol/L. The formation of thromboxane B2 (TXB2) and 12-hydroxy-5,8,10-heptadecatrienoic acid (HHT), the final metabolites in the pathway of cyclooxygenase-thromboxane synthetase, were decreased from 24 +/- 6.7 to 3.2 +/- 1.6% and 10.3 +/- 2.49 to 4.7 +/- 2.8%, respectively. Meanwhile, 12-hydroxy-5,8,10,14-eicosatetraenoic acid (12-HETE), the metabolite in the pathway of lipoxygenase, was increased from 11.9 +/- 1.7 to 34 +/- 5.6%. It is suggested that NMPA blocks the pathway of cyclooxygenase-thromboxane synthetase and then changes the direction of arachidonate metabolism in platelets, the activation of platelets is inhibited in this way.